Fast thickness gauging with an ECOPS-based terahertz time-domain system - Yahyapour, M.; Jahn, A.; Dutzi, K.; Puppe, T.; Leisching, P.; Schmauß, Bernhard; Vieweg, N.; Deninger, A. (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
We employ thickness gauging with a fast terahertz time-domain spectroscopy (TDS) system based on electronically controlled optical sampling (ECOPS) and compare the results with those of a benchmark conventional terahertz TDS system and a mechanical micrometer gauge. The results of all technologies are in good agreement. We show that the ECOPS system is suitable for fast inline thickness measurements, owing to high measurement rate of 1600 traces per second. Moreover, we characterize the system with respect to signal quality. The time-domain dynamic range is ∼60 dB for a single-shot measurement, and ∼90 dB with 1000 trace averages, which are completed within less than a second (i.e., 0.625 seconds). The time-domain signal-to-noise ratio amounts to ∼50 dB and ∼80 dB for 1 and 1000 averages, respectively.
CRIS-Team Scopus Importer:2020-05-02
Keywords: ECOPS; Non-destructive testing; Real-Time inspection; Terahertz time-Domain instrumentation; Thickness gauging